Tannerella forsythia: important pathogen in periodontitis, member of the red complex - Ramos-Perfecto, Donald (2020)
Among the microorganisms that form the red complex, considered by Socransky as aggressive bacteria in periodontitis, such as Tannerella forsythia, a strict anaerobic bacillus, which would be participating with relevance in this pathology, its multiple virulence factors, as well as its capacity to subsist under optimal conditions in the periodontal pocket, such as stimulating the activation of inflammation mediators that with the chronicity of the disease would be progressively damaging the periodontium. In this review, we will learn more regarding this microorganism of great importance in periodontal diseases.